MODIFICATION OF STRAW MEDIA IN BOARDING SCHOOL BASED FLOOR GYMNASTICS LEARNING - Prianto, Dian; Yono, Topo (Gladi : Jurnal Ilmu Keolahragaan, 2025)
This study uses survey and observation methods at SMK Islam Bustanul Athfal. Ulum Pakusari, the lack of infrastructure, especially mat media, makes learning less effective and efficient. Many students wait for their turn when doing floor gymnastics. In this study, a modification was carried out to create a simple alternative modification of rice straw as a supporting tool for floor gymnastics learning. Modified rice straw measuring 60x120 cm, 30 cm thick, requires a stable balance in its manufacture with straw media as a solution for floor gymnastics learning. The method used is to define, interpret, and explain a situation. The learning process using straw media modifications is very helpful in overcoming the lack of facilities at SMK Islam Bustanul Ulum. Straw is easy to use and as a supporting tool for learning.